One-step detection of human papilloma viral infection using quantum dot-nucleotide interaction specificity - Jimenez Jimenez, Ana Maria; Moulick, Amitava; Bhowmick, Sukanya; Strmiska, Vladislav; Gagic, Milica; Horakova, Zuzana; Kostrica, Rom; Masarik, Michal; Heger, Zbynek; Adam, Vojtech (Talanta, 2019)
Due to the close relationship between carcinogenesis and human papillomavirus (HPV), and since they are transmitted via huge number of asymptomatic carriers, the detection of HPV is really needed to reduce the risk of developing cancer. According to the best of our knowledge, our study provides the very first method for one-step detection of viral infection and if it has initiated the subsequent cancer proliferation. The proposed novel nanosystem consists of magnetic glass particles (MGPs), which were attached with DNA probe on their surface to hybridize with target DNAs. The MGP-probe-DNA hybrid was finally conjugated with CdTe/ZnSe core/shell quantum dots (QDs). The proposed detection system is based on a novel mechanism in which the MGPs separate out the target DNAs from different biological samples using external magnetic field for better and clear detection and the QDs give different fluorescent maxima for different target DNAs due to their ability to interact differently with different nucleotides. Firstly, the method was optimized using HPV genes cloned into synthetic plasmids. Then it was applied directly on the samples from normal and cancerous cells. After that, the real hospital samples of head and neck squamous cell carcinoma (HNSCC) with or without the infection of HPV were also analyzed. Our novel nano-system is proved successful in detecting and distinguishing between the patients suffering by HPV infection with or without subsequent cancer having detection limit estimated as 1.0 x 109 (GEq/mL). The proposed methodology is faster and cost-effective, which can be applied at the clinical level to help the doctors to decide the strategy of medication that may save the life of the patients with an early treatment.
Keywords: Limit of Detection; Microscopy, Fluorescence; Cancer; Spectrometry, Fluorescence; limita detekce; Nanotechnology; Humans; Biosensing Techniques; Tellurium; sklo; fluorescenční spektrometrie; Squamous Cell Carcinoma of Head and Neck; fluorescenční mikroskopie; Aged; dospělí; senioři; lidé; magnetické jevy; biosenzitivní techniky; Human papillomavirus; Papillomaviridae; Adult; Papillomavirus Infections; Male; DNA Probes; Magnetic isolation; DNA virů; dlaždicobuněčné karcinomy hlavy a krku; DNA, Viral; nádorové buněčné linie; infekce papilomavirem; Cadmium Compounds; Nucleic Acid Hybridization; telur; Quantum dots; hybridizace nukleových kyselin; Cell Line, Tumor; Magnetic Phenomena; Quantum Dots; sloučeniny kadmia; mužské pohlaví; Glass; kvantové tečky; DNA sondy